2018
DOI: 10.14710/reaktor.17.4.197-202
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Oil Palm Empty Fruit Bunch Enzymatic Hydrolysis

Abstract: As lignocellulosic biomass, Oil Palm Empty Fruit Bunch (OPEFB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[25] and Meilany et al [26] reported the optimum temperature for xylan hydrolysis for obtaining the highest xylose yield at 60 °C. In contrast, Pappu and Gummadi [37] and Sánchez et al [28,39] reported the optimum temperature for fermentation at 35 °C.…”
Section: Mapping the Effects Of Temperature On Hydrolysis And Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] and Meilany et al [26] reported the optimum temperature for xylan hydrolysis for obtaining the highest xylose yield at 60 °C. In contrast, Pappu and Gummadi [37] and Sánchez et al [28,39] reported the optimum temperature for fermentation at 35 °C.…”
Section: Mapping the Effects Of Temperature On Hydrolysis And Fermentationmentioning
confidence: 99%
“…However, the optimum temperature for conducting hydrolysis and fermentation simultaneously has been overlooked; the SSF was conducted at the optimum fermentation temperature, leading to low enzymatic hydrolysis activity. The optimum temperature of xylan hydrolysis using xylanase is reported in the range of 40-70 °C [25,26], whereas the optimum temperature for xylitol-producing yeast fermentation is reported in 10-44 °C [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimum temperature for conducting both hydrolysis and fermentation simultaneously has been overlooked, the SSF was conducted at the optimum fermentation temperature that led to low enzymatic-hydrolysis activity. The optimum temperature of xylan hydrolysis using xylanase is reported in the range of 40-70 o C [26,27], whereas the optimum temperature for xylitol-producing yeast fermentation is reported in the range of 10-44 o C [28][29][30][31]. Conducting the SSF at the optimum temperature for both hydrolysis and fermentation would significantly increase the process performance.…”
Section: Introductionmentioning
confidence: 99%